2023
DOI: 10.1371/journal.pone.0286322
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vaccine perception and vaccination intention of Mpox infection among the adult males in Bangladesh: A cross-sectional study findings

Abstract: Background Mpox (monkeypox) infection has become a global concern for healthcare authorities after spreading in multiple non-endemic countries. Following the sudden multi-country outbreak of Mpox, the World Health Organization (WHO) declared a public health emergency of international concern. We do not have any vaccines approved for the prevention of Mpox infection. Therefore, international healthcare authorities endorsed smallpox vaccines for the prevention of Mpox disease. Here we intended to perform this cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…The present study had similar findings, such as the associations between perceived susceptibility to and severity of mpox and the intention to vaccinate against mpox, compared to previous studies in the general population [ 19 , 20 ]. However, the present study found that older MSM were more likely to receive an mpox vaccination, and the result was contrary to that of two previous studies, indicating the difference in the factors related to the intention to vaccinate against mpox between the general and MSM populations [ 17 , 18 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study had similar findings, such as the associations between perceived susceptibility to and severity of mpox and the intention to vaccinate against mpox, compared to previous studies in the general population [ 19 , 20 ]. However, the present study found that older MSM were more likely to receive an mpox vaccination, and the result was contrary to that of two previous studies, indicating the difference in the factors related to the intention to vaccinate against mpox between the general and MSM populations [ 17 , 18 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have examined the factors related to the intention to vaccinate against mpox. Studies in the general population have revealed that sociodemographic characteristics (such as male sex, younger age, nonheterosexual orientation, higher education level, and urban residence); cognitive appraisal (such as higher perceived susceptibility to and severity of mpox, increased knowledge of mpox, lower conspiracy beliefs about mpox, greater emotional fear of mpox, and higher perceived potential of the occurrence of a pandemic); confidence in vaccination; and collective responsibility are significantly associated with a higher intention to vaccinate against mpox [ 16 , 17 , 18 , 19 , 20 , 21 ]. Studies involving MSM have revealed that those ones who are gay, spend more time with other gay or bisexual men, have good knowledge of mpox, have higher perceived susceptibility to mpox, have no steady relationship, and have low constraints on vaccine access are more likely to receive mpox vaccination [ 11 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…People in the United States with a higher risk perception wanted to get vaccinated against COVID‐19 47 . Little is known about the impact of subjective norms on Mpox vaccine acceptance, although previous studies on COVID‐19 vaccines indicated that subjective norms perception influenced the acceptability of COVID‐19 vaccination 48,49 . As a result, we can predict that in the Mpox situation, people with higher subjective norms may show their agreement with Mpox vaccines.…”
Section: Discussionmentioning
confidence: 95%
“…47 Little is known about the impact of subjective norms on Mpox vaccine acceptance, although previous studies on COVID-19 vaccines indicated that subjective norms perception influenced the acceptability of COVID-19 vaccination. 48,49 As a result, we can predict that in the Mpox situation, people with higher subjective norms may show their agreement with Mpox vaccines. Since most of our participants possess a moderate-to-high risk perception and subjective norms, they may perceive a positive attitude toward vaccination in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Other socioeconomic factors such as marital status, social income, and educational level may have some influence on the willingness to be vaccinated [ 62 ]. However, this was not clearly described in the included studies, with a huge difference in age groups, marital status subdivisions, different educational levels, and social income levels.…”
Section: Discussionmentioning
confidence: 99%